Melanosis coli in a peritoneal dialysis patient: a case report - Zakaria, Nor Fadhlina; Ahmad, Nurul Izah; Mokhtar, Elmina; Wan Zukiman, Wan Zul Haikal Hafiz; Md Shah, Anim (BioMed Central, 2021)
Background: Patients who undergo peritoneal dialysis (PD) are at risk of gut bacteria translocation leading to peritonitis when there is chronic diarrhea. Chronic diarrhea is defined as any course of diarrhea that lasts at least 4 weeks, which can be continuous or intermittent. Chronic diarrhea of any duration may cause dehydration, electrolyte imbalance, and life-threatening hypovolemic shock. In PD patients, excessive ultrafiltration from the exchanges, combined with severe gastrointestinal loss, may cause hypovolemic shock, electrolyte imbalance, and metabolic acidosis. There are multiple causes of chronic diarrhea in PD patients including infective causes, mitotic lesions, and rarely the regular and excessive use of laxatives, which is a diagnosis of exclusion. Case presentation: We report a case of Melanau lady with chronic diarrhea secondary to laxative usage in a patient being treated with automated peritoneal dialysis (APD). The patient went into hypovolemic shock, but luckily did not contract peritonitis. A colonoscopy revealed brown to black discoloration of the colon, a feature suggestive of melanosis coli. A biopsy of the intestine further confirmed the diagnosis by histopathological examination. Withdrawal of laxatives and the introduction of probiotics improved the symptoms tremendously. Conclusions: The chronic use of laxatives in PD patients can potentially lead to a devastating problem; thus, the management team must monitor treatment commencement appropriately.